2012
DOI: 10.1177/1076029612452116
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neutrophil to Lymphocyte Ratio and Severity of Coronary Artery Disease

Abstract: The aim of this study is to investigate the association between neutrophil to lymphocyte ratio (NLR) and severity of coronary atherosclerosis. A total of 172 patients undergoing coronary angiography were included in the study. Control group consisted of patients with normal coronary arteries. Patients with coronary stenosis were divided into 2 groups by use of Gensini scores. The NLR was higher in severe atherosclerosis group compared with mild atherosclerosis and control groups (P < .001). In correlation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 20 publications
7
113
1
6
Order By: Relevance
“…In that study of 287 patients, the NLR was found to be significantly correlated with the SYNTAX score in both the ST elevation myocardial infarction (STEMI) and NSTE-ACS groups 35) . Furthermore, three other studies reported this relationship in SAP populations 15,36,37) . Kaya H. et al 36) used the Gensini score, whereas Sönmez O. et al 15) and Kaya A. et al 37) used the SYNTAX score, to assess the severity and complexity of CAD.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…In that study of 287 patients, the NLR was found to be significantly correlated with the SYNTAX score in both the ST elevation myocardial infarction (STEMI) and NSTE-ACS groups 35) . Furthermore, three other studies reported this relationship in SAP populations 15,36,37) . Kaya H. et al 36) used the Gensini score, whereas Sönmez O. et al 15) and Kaya A. et al 37) used the SYNTAX score, to assess the severity and complexity of CAD.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, three other studies reported this relationship in SAP populations 15,36,37) . Kaya H. et al 36) used the Gensini score, whereas Sönmez O. et al 15) and Kaya A. et al 37) used the SYNTAX score, to assess the severity and complexity of CAD. Rather consistently, the NLR was found to be an independent predictor of a high Gensini or SYNTAX score in these studies.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous studies have shown that severity of CAD is correlated with higher NLR value. Kaya et al [20] showed that NLR is a predictor of severe atherosclerosis, which may be useful for cardiac risk stratification in patients with CAD. They showed significant correlation between NLR and GENSINI score.…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been shown to predict short and longterm mortality in patients with both ST and non-ST elevation myocardial infarction and in patients undergoing percutaneous coronary interventions. 10,11,17,18 NLR has also been shown to be predict severity of coronary artery disease 19 and patency of bare metal stents after percutaneous coronary interventions and saphenous vein grafts after coronary artery bypass surgery. 20,21 Despite this, relatively few studies have investigated the NLR in patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%